Stabilization of Black Cotton Soil by Using Waste Foundry Sand and Crushed Waste Glass (International Journal of Innovative Research in Computer Science & Technology, 2023)
Generally Black Cotton Soil exhibits  undesirable engineering properties like shrinkage and  swelling properties losses its strength, when come in contact  with water. Thereby poor bearing capacity and higher  compressibility. Thus the improvement of soil at a site is  indispensable. There are many methods and stabilizers to  improve the strength of soil like jute, gypsum, fly ash.  Rice-husk ash. Cement, lime, used rubber tyres etc. In the  present study, we added Waste Foundry Sand and Crushed  Waste Glass as stabilizer to improve the properties of Black  Cotton soil. Black Cotton Soil used in this project work is  carried from Maharashtra. The objective of this study is to  improve the strength of the Black Cotton soil by making  Soil- Waste Foundry Sand and Soil- Waste Foundry Sand Crushed Glass Powder mixture. Specimens is to be prepared  to investigate the properties of soil out of these specimens  are prepared by Replacing 2 %, 4%, 6% . Waste Glass  Powder with varying percentage Waste Foundry Sand as  10%,20%, 30%.[4] Modified Proctor Test, CBR test and  Free Swell Index test is to be conducted to analyze the  Optimum Moisture Content (OMC), Maximum Dry Density  (MDD) and compressive strength of soil mixture, CBR value  and Free Swell Index.
Keywords: Black Cotton Soil; Crushed Waste Glass; Strength of Soil; Modified Procter Test; BC Soil MDD; OMC; WFS; WGP; BC Soil Stabilization